Robotic Transanal Minimally Invasive Surgery for Rectal Polyps - Friedman, Garrett; Rodriguez, Miguel (Clinics in Colon and Rectal Surgery, 2023)
Transanal minimally invasive surgery (TAMIS) can be utilized to manage a wide variety of rectal lesions but can be technically demanding with traditional laparoscopic equipment. Robotic platforms such as the da Vinci Single Port system can reduce the technical barriers of TAMIS and allow more complicated lesions to be addressed. Robotic TAMIS with the SP system follows similar indications for local excision of benign and malignant lesions as conventional TAMIS or even transanal endoscopic microsurgery. We describe our initial experience using the SP system and provide technical suggestions for how to incorporate this technology. We also address innovations in flexible endoscopic robotic surgery that we anticipate will allow for increased use of organ preservation of the colon and rectum, as well as possibly expand the use of natural orifice surgery.
Keywords: TAMIS; endoluminal surgery; rectal polyp; TEM; robotic surgical platforms